Aedes (Ochlerotatus) excrucians - Khalin, A. V.; Aibulatov, S. V. (Zenodo, 2021)
Aedes ( Ochlerotatus ) excrucians (Walker,1856) Northernmost records (Fig. 3b). 69°24 ′ 36.13 ″ N, 30°12 ′ 36.23 ″ E, MP, Pechenga Distr., Nikel’ (Sharkov, 1980); 68°50 ′ 4.39 ″ N, 58°8 ′ 38.39 ″ E, NAR, Pechora Sea near Prirazlomnaya offshore fixed platform, aboard vessel, 21–24.VII.2018 (MOC); 67°29 ′ 50.68 ″ N, 64°3 ′ 39.93 ″ E, Komi, Vorkuta Distr., Vorkuta (Panyukova & Ostroushko, 2017). Distribution . NWR: AP, Komi, KP, LP, MP, NAR, NP, PP, RK, SPb, VP. Adjacent countries: Norway, Sweden, Finland, Estonia, Latvia, Lithuania and Belarus. Europe (ranging northward to the Netherlands, Germany, Denmark and Poland); the Holarctic. Published as part of Khalin, A. V. & Aibulatov, S. V., 2021, Northernmost records of mosquito species (Diptera: Culicidae) in northwestern Russia, pp. 46-63 in Zoosystematica Rossica (Zoosyst. Rossica) (Zoosyst. Rossica) 30 (1) on page 55, DOI:10.31610/zsr/2021.30.1.46, http://zenodo.org/record/10124237